2023
DOI: 10.3389/feduc.2023.976906
|View full text |Cite
|
Sign up to set email alerts
|

The influence of self-esteem, depression, and life satisfaction on the future expectations of Peruvian university students

Abstract: IntroductionStrengthening the self-confidence of future professionals can help them achieve professional goals with a likelihood of being able to achieve them in the future. The objective was to determine whether self-esteem, depression, and life satisfaction influence the future expectations of Peruvian university students.MethodsA total of 708 university students participated (64.8% were female, mean age = 21.49; SD = 4.83). The Rosenberg Self-Esteem Scale, the Patient Health Questionnaire-2, the Life Satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…(43) Existen teorías que respaldan el hallazgo expuesto. Por ejemplo, la Teoría de la Autoeficacia de Bandura (58) postula que las creencias de una persona sobre su capacidad para enfrentar y superar los desafíos influyen en su bienestar general y su satisfacción con la vida. Además, la Teoría del Apoyo Social, propuesta por House, (59) sugiere que la presencia de redes de apoyo social puede proporcionar recursos emocionales y prácticos que contribuyen al bienestar psicológico y la satisfacción con la vida.…”
Section: Discussionunclassified
“…(43) Existen teorías que respaldan el hallazgo expuesto. Por ejemplo, la Teoría de la Autoeficacia de Bandura (58) postula que las creencias de una persona sobre su capacidad para enfrentar y superar los desafíos influyen en su bienestar general y su satisfacción con la vida. Además, la Teoría del Apoyo Social, propuesta por House, (59) sugiere que la presencia de redes de apoyo social puede proporcionar recursos emocionales y prácticos que contribuyen al bienestar psicológico y la satisfacción con la vida.…”
Section: Discussionunclassified
“…Especially in times of confinement, where the frequency of use of social networks such as Instagram, Facebook or Twitter has increased significantly, generating problems of body dissatisfaction or low self-esteem, which alter the perception of personal valuation (Pyszczynski et al, 2021). Current research has proven the association between this variable and life satisfaction, as revealed by a study conducted with 1,117 Spanish adolescents, where self-esteem played a moderating role between empathy and life satisfaction (Usán et al, 2023); likewise, other studies have shown that there is a functional relationship in Peruvian university students (Mamani-Benito et al, 2023) and Norwegian adolescents (Moksnes et al, 2022). Based on this evidence it is assumed to have a predictive power to explain satisfaction with life, as studies report that individuals who negatively self-evaluate themselves are not satisfied with their own lives, in contrast to those who positively self-evaluate themselves (Naranjo Pereira, 2007;Cid-Sillero et al, 2020).…”
Section: Literature Review: Predictors Of Life Satisfaction In Univer...mentioning
confidence: 97%
“…More specifically, it highlights the individual's subjective assessment of the satisfaction with their current life based on self-established standards [20,21]. Satisfaction from life is considered a very important parameter in HE, not only due to its positive relationship with higher academic performance but also because it has the potential to enhance students' future expectations, overall academic experience, relationships, and psychological well-being [22,23]. However, students' living conditions underwent a drastic transformation during the pandemic, and it is reasonable to assume that their assessment of life standards changed accordingly.…”
Section: Life Satisfaction In University Studentsmentioning
confidence: 99%